2023
DOI: 10.7717/peerj.15917
|View full text |Cite
|
Sign up to set email alerts
|

Icariin activates far upstream element binding protein 1 to regulate hypoxia-inducible factor-1α and hypoxia-inducible factor-2α signaling and benefits chondrocytes

Pengzhen Wang,
Pingping Zhu,
Shaoheng Zhang
et al.

Abstract: Icariin (ICA) is a typical flavonoid glycoside derived from epimedium plants. It has both anabolic and anti-catabolic effects to improve bone mineral density and reduce bone microstructural degradation. However, the effect and underlying mechanism of ICA on the proliferation and metabolism of chondrocyte and synthesis of extracellular matrix are still unclear. This study aimed to investigate the role and regulation of far upstream element binding protein 1 (FUBP1) in chondrocytes treated with ICA to maintain h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…This helps maintain a balance where the formation of new bone exceeds the rate of bone degradation. 13 , 14 This property is particularly advantageous in the prevention and treatment of OP. Recent studies have demonstrated the potential of Epimedin C (EC), an active ingredient of Epimedium, in treating OP, especially GIOP.…”
Section: Introductionmentioning
confidence: 99%
“…This helps maintain a balance where the formation of new bone exceeds the rate of bone degradation. 13 , 14 This property is particularly advantageous in the prevention and treatment of OP. Recent studies have demonstrated the potential of Epimedin C (EC), an active ingredient of Epimedium, in treating OP, especially GIOP.…”
Section: Introductionmentioning
confidence: 99%